Becomings of school-fathers: An Ethnographic Exploration of Migrant Fathers’ Experiences and Navigation of Home-School Cooperation - Jørgensen, Anne Hovgaard (AU Library Scholarly Publishing Services, 2020)
This PhD dissertation investigates migrant fathers’ experiences of home-school cooperation. Based on ethnographic fieldwork in a public school in Copenhagen, a social housing complex and various fathers’ groups, the dissertation sheds light on how migrant fathers are navigating the terrain of home-school cooperation differently, and how certain constrains in these interlocutors’ lives hindered some fathers from performing as "visible" and "active" fathers - performances, appreciated by the school. The dissertation also identifies a social phenomenon termed as mistrusted masculinity. We see how certain negative controlling images of the Muslim, migrant man, is figuring in political and media rhetoric, where this ’kind of man’ is represented as controlling, a patriarch and as a brake on integration and equality of gender. Migrant fathers express how they, in various ways, had to relate and navigate according to this negative controlling image, in their struggle to be acknowledged as good school-fathers.